Cytotoxic Activity of Taraxacum officinale Ethanolic Plant Extract against Human Breast Cancer (MCF-7) Cells and Human Hepatic (WRL-68) Cells - Muhammed, Rawa’a A. (Iraqi Journal of Cancer and Medical Genetics, 2018)
Taraxacum officinale (Dandelion) represent a potentially novel non-toxic alternative to conventional cancer therapy towardmany cancers particularly breast cancer.This study was conducted to detect the cytotoxic activity of T. officinale whole plant ethanolic extract on human breast cancer(MCF-7) cells in vitro compared to human hepatic (WRL-68) cells using MTT assay.Graphed 6 prism program including non-linear regression with one –way ANOVA followed by Dennett’s multiple comparisontest to obtain data represent the mean+ SD.The results revealed high toxicity of the extract against MCF-7 cells with IC50 (190.5 μg.ml-1) and showed high-reducedactivity toward WRL-68 cells with high IC50 value while the lowest viability (21.57±5.322) appeared in MCF-7 cells undertreatment with 400 μg.ml-1 compared with high viability in WRL-68 cells.The study concluded that T. officinale extract has a valuable source of anticancer drugs with safe and selective activity oncancer cells in comparison to human normal cells.